Diabetes Mellitus and Bone Metabolism - Kasperk, Christian; Georgescu, Carmen; Nawroth, Peter (Experimental and Clinical Endocrinology & Diabetes, 2017)
Diabetes mellitus and bone metabolism affect mesenchymal tissues and have numerous epidemiological and pathophysiological associations in common. Diabetes mellitus affects bone metabolism and increases fracture risk. The pathophysiological mechanims how type 1 and type 2 diabetes impair bone metabolism and bone strength may differ which is outlined in this review. Direct metabolic effects in additon to centrally controlled endocrine loops exert suppressive effects on bone formation and may also stimulate bone Resorption. Decreased bone formation in combination with increased bone resorption strongly increases fracture risk.
Keywords: bone; fracture risk; energy metabolism; Diabetes<Autoimmunity; osteoporosis